The structure and function of the cervix during pregnancy - James P. Nott; Elizabeth A. Bonney; James D. Pickering; Nigel A.B. Simpson (Elsevier, 2016)
The structure of the cervix is integral to the maintenance of pregnancy, keeping the developing baby in utero and forming a barrier to the ascent of microorganisms from the vagina. Weakness of the cervix may lead to deficiency of this barrier and is associated with subsequent preterm birth. The underlying cause of this structural weakness is poorly understood. In this paper we review the structure and function of the cervix before and during pregnancy. The causes of mechanical failure of the cervix during pregnancy are described, with a specific focus on the internal cervical os. We highlight the role of the internal cervical os in causing preterm birth and discuss research techniques that may provide further insight into its function during pregnancy. It is hoped that clinical translation of this knowledge will enable the early and appropriate identification of women who will benefit from strategies to reinforce the internal os and so reduce the incidence of preterm birth. Keywords: Cervix, Pregnancy, Preterm birth, Cervical weakness